2004
DOI: 10.1017/s095283690400593x
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory behaviour of gravid and non‐gravid female grass snakes (Natrix natrix) in a thermally limiting high‐latitude environment

Abstract: All else being equal, ectotherms should maintain body temperatures (T b s) favourable for temperature-sensitive biological functions, such as digestion and locomotion. Physical environments in the temperate zone are often thermally variable, however, thus making it difficult to maintain optimum T b s. Radiotelemetry and a semi-natural enclosure were used to monitor T b s of grass snakes Natrix natrix at Canterbury, Kent, U.K. Operative temperatures (T e s) were measured using snake models (copper-pipe models) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 42 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…Nonetheless, while this response holds for some snakes species (e.g. BROWN & WEATHERHEAD 2000, LADYMAN et al 2003 including tropical ones (LUISELLI & AKANI 2002, CHIARAVIGLIO 2006, it is absent in others (SANDERS & JACOB 1981, ISAAC & GREGORY 2004. For B. insularis we found that the T b of gravid females conformed to the general relationship between T b and T e , which indicates no change in thermoregulatory behaviour.…”
Section: Discussionmentioning
confidence: 49%
“…Nonetheless, while this response holds for some snakes species (e.g. BROWN & WEATHERHEAD 2000, LADYMAN et al 2003 including tropical ones (LUISELLI & AKANI 2002, CHIARAVIGLIO 2006, it is absent in others (SANDERS & JACOB 1981, ISAAC & GREGORY 2004. For B. insularis we found that the T b of gravid females conformed to the general relationship between T b and T e , which indicates no change in thermoregulatory behaviour.…”
Section: Discussionmentioning
confidence: 49%
“…It would therefore be informative to examine intersexual differences in T b in March and April to further examine this hypothesis. In a similar manner, normal embryonic development is dependent on temperature (Lillywhite, 1987), and females may thermoregulate to achieve high T b to aid embryonic development during the summer gestation period (Charland, 1995;Gregory et al, 1999;Isaac and Gregory, 2004;Kapfer et al, 2008). Thermoregulatory behavior has a strong influence on the duration of gestation and fitness of offspring in viviparous squamates (Shine and Harlow, 1993;Lourdais et al, 2004); therefore, natural selection may act upon females to thermoregulate precisely while gravid (Shine and Harlow, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, maternal temperature during different stages of development affects the number of body segments, developmental rate, and the incidence of stillbirths in the Aspic Viper (Vipera aspis; Lourdais et al, 2004). If thermoregulation to high T b has associated costs, such as increased predation risk (Huey and Slatkin, 1976;Peterson, 1987;Charland, 1995;Isaac and Gregory, 2004), reduced T b may be an adaptive response when fitness benefits of reproductive activity are not imperative. Alternatively, differing T b may be a consequence of differences in behavior, rather than causing differences in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas changes in thermoregulatory behavior attributable to reproductive condition have been well documented for viviparous snake species (e.g., Graves and Duvall, 1993;Charland, 1995;Dorcas and Peterson, 1998;Brown and Weatherhead, 2000), the subject has been investigated to a lesser extent in oviparous taxa (e.g., Blouin-Demers and Weatherhead, 2001a;Isaac and Gregory, 2004). This disparity is due at least partly to the relatively shorter period of egg retention in oviparous species, with the consequent effect of making changes in thermoregulatory behavior (e.g., increased basking) less amenable to casual observation or quantification.…”
mentioning
confidence: 99%